A Brief Introduction to Impact: 'The Meme Font'. (December 2014) - Brideau, Kate; Berret, Charles
If you have ever seen an image macro, the chances are you've seen Impact, a typeface so commonly used in these memes that it could be called 'the meme font'. Its ubiquity within image macros is largely overlooked, yet it contributes significantly to their structure, and raises productive questions about creativity and the balance of replication and variation in memes more generally. This article is a brief introduction to Impact – its design and its history – as it relates not only to the practice of typography, but also to the development of standards for operating systems and for the web. Impact, like internet memes themselves, tells a story of both standardization and innovation. This typeface lay largely dormant for decades after its design, but today it ensures its own proliferation through its fixed role in the production of image macros.